Carbon dioxide adsorption material with bionic lung trachea structure
By constructing a staged open-pore channel and macroscopic nano/micrometer closed-celled bionic lung tracheal structure carbon dioxide adsorption materials in amorphous aluminosilicate, the existing adsorbents' renewable energy density, high cost and low stability are solved, and an efficient, economical and mechanically stable carbon capture effect is achieved.
Patent Information
- Application Number
- CN202510166384.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-15
AI Technical Summary
The existing carbon capture adsorbents have energy-intensive regeneration problems, high raw material costs, complex preparation process, and low stability and gas transmission rate, which limit their large-scale application in industry.
Using carbon dioxide adsorption material with a bionic lung tracheal structure, the rapid transmission and large-scale storage of gases are achieved by constructing step-by-step open-cell channels and macro nano/micro-closed cells in amorphous aluminosilicate, and hydrogen peroxide foaming and foam stabilizing agents are used to adjust the pores, so as to achieve rapid transmission and large-scale storage of gases.
It significantly improves the adsorption amount, adsorption rate and cyclic stability of carbon dioxide, reduces the preparation cost, and the material has excellent mechanical stability, which is suitable for industrial applications.
Smart Images

Figure CN119819252A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon capture, and in particular to a carbon dioxide adsorption material with a bionic lung trachea structure. Background Art
[0002] The development of efficient and economical carbon capture adsorbents is the key to achieving industrial carbon neutrality. Organic amine solutions are currently one of the most widely used carbon dioxide absorbents in industry. They react with weak acids (CO2) and weak bases (amines) to form water-soluble salts by contacting flue gas with the solution. Although organic amines are efficient in absorbing carbon dioxide, their regeneration is energy-intensive and the absorbents are prone to chemical decomposition. Therefore, there is an urgent need to find economical, safe and efficient alternatives to organic amine solutions.
[0003] The adsorption of carbon dioxide by solid adsorbents in the carbon capture process is a step reaction, which has multiple advantages such as fast, stable, high number of cycles and low cost. Solid adsorbents can achieve carbon capture through the combined action of physical adsorption, chemical adsorption and chemical mineralization. Chemical adsorption materials usually have higher capacity and selectivity. Porous materials are ideal carbon dioxide adsorbents, including activated carbon, zeolites, MOFs and hydrotalcites. Patent CN 116062751A obtains coal-based activated carbon with rich pores by treating the original coal to achieve efficient adsorption of carbon dioxide. At the same time, the doping of nitrogen and boron elements significantly increases the active sites and micropores of the adsorbent. Patent CN 117699815A uses transition metal / alkali metal carboxylates and inorganic acid to modify the pores, framework polarity and coordinated cations of zeolites, which increases the adsorption capacity of carbon dioxide by 20%-40%. Patent CN 116037078A reports a new type of multi-metal MOF material, whose carbon dioxide adsorption capacity is nearly 15% higher than that of commercial Mg-MOF-74. Patent CN 117025272A significantly improves the specific surface area, pore volume and pore size of magnesium aluminum hydrotalcite by roasting, achieving efficient capture of carbon dioxide in biogas. However, the above adsorbent still has the problems of high raw material cost and complicated preparation process, which restricts its large-scale application in industry.
[0004] Nano / micron-scale sizes or pores also reduce the stability and gas transfer rate of existing adsorbent materials. Industrially, any absorption time exceeding 5 minutes will greatly increase costs. Ideally, 80% of carbon dioxide absorption should be completed within 2 minutes. Small and uniform pores usually significantly reduce the diffusion of carbon dioxide. In terms of gas transfer rate, the lungs are the most efficient O2 absorption and CO2 desorption machines, attributed to the diffusion paths created by its channels of various sizes. Therefore, it is of great practical significance to develop low-cost, easy-to-prepare CO2 adsorbents with bionic lung tracheal structures. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a carbon dioxide adsorption material with a bionic lung trachea structure, which has stepped open pores and a large number of nano / micro closed pores to achieve rapid gas transmission and large-scale storage; carbon dioxide is captured through pore regulation, and the cycle stability is better.
[0006] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing a carbon dioxide adsorbent material with a bionic lung trachea structure is provided, comprising the following steps:
[0007] S1. dissolving alkali and active silica in the landfill leachate concentrate containing a foam stabilizer, stirring until completely dissolved, and aging to obtain a mixed solution;
[0008] S2, adding activated alumina to the mixed solution obtained in step S1, stirring until viscous, to obtain a slurry;
[0009] S3, adding hydrogen peroxide to the slurry obtained in step S2, stirring evenly and letting it stand for foaming, then filling it into a silicone mold, and then sealing, curing and demoulding in sequence to obtain a carbon dioxide adsorption material with a bionic lung trachea structure.
[0010] Furthermore, in step S1, the alkali is sodium hydroxide or potassium hydroxide; and the active silicon dioxide is sodium silicate or potassium silicate.
[0011] Furthermore, in step S1, the foam stabilizer is at least one of lignin, molasses, humic acid and fulvic acid; and its content is 80-2000 mg / L in terms of dissolved organic carbon.
[0012] Further, in step S1, aging is performed for 12 hours, and stirring is performed again 2-3 times during the aging period.
[0013] Furthermore, in step S1, the organic matter content in the landfill leachate concentrate is greater than 85%.
[0014] Furthermore, in step S2, the activated alumina is at least one of metakaolin, ground blast furnace slag, fly ash and red mud.
[0015] Furthermore, in step S2, the liquid-to-solid ratio of the slurry is 0.5-0.7.
[0016] Furthermore, in steps S1 and S2, the mass ratio of alkali, activated silica and activated alumina is 3-7:18-22:3-7.
[0017] Furthermore, in step S3, the amount of hydrogen peroxide added is 0.5-3wt% of the slurry.
[0018] Further, in step S3, the silicone mold is sealed with plastic wrap and cured at a temperature of 40-70° C. for 12 hours.
[0019] The preparation method of the present invention is inspired by the efficient O2 absorption and CO2 desorption of the human lungs. Hydrogen peroxide foaming and foam stabilizers are used to construct stepped open-pore channels and macro-micrometer / nanometer closed pores in amorphous aluminosilicates, simulating the bronchi connected to the lungs and hundreds of millions of tiny alveoli. The CO2 adsorption capacity, adsorption rate and cyclic stability of the prepared adsorbent material are significantly improved compared to those of non-opened and powdered aluminosilicates. The raw materials for preparing the adsorbent material provided by the present invention are mainly cheap and readily available natural minerals or industrial wastes. The preparation process does not involve energy-intensive processes such as high temperature, ball milling and hydrothermal, and is a mechanically stable block material with great industrial application value.
[0020] The present invention also provides a bionic lung trachea structure carbon dioxide adsorbent material prepared by the preparation method of the bionic lung trachea structure carbon dioxide adsorbent material, such as Figure 1 shown.
[0021] The present invention has the following beneficial effects:
[0022] 1. The present invention utilizes active silicon dioxide and aluminum oxide to undergo a dissolution-reconstruction-polymerization-condensation reaction under alkaline conditions to form amorphous aluminosilicates, which have a stable three-dimensional network skeleton support structure. The oxygen generated by the decomposition of hydrogen peroxide under alkaline conditions diffuses outward to form continuous open-pore channels, similar to the large number of bronchi in the lungs, to achieve rapid gas transmission. The foam stabilizer reduces the surface tension of the bubbles, prompting the bubbles to disperse inward to form a large number of micron / nano closed pores, similar to the large number of alveoli in the lungs, to achieve large-scale gas storage. The large number of ≡Si-OH / ≡Al-OH active sites on the surface of the amorphous aluminosilicate structure realize the selective adsorption of CO2.
[0023] 2. The block carbon dioxide adsorption material of the bionic lung trachea structure of the present invention has a stepped pore structure, which is conducive to rapid gas transmission and large-scale storage, while the pore size of traditional adsorption materials is micro-nano pores and the pore structure is single, and the absorption / desorption rate of CO2 is slow.
[0024] 3. The present invention realizes the simple preparation of bulk adsorption materials by forming amorphous aluminosilicates, which have excellent mechanical stability, while traditional adsorption materials are all powders or nanomaterials, which are easily damaged by the mechanical impact of the cyclone separator.
[0025] 4. The preparation cost of the present invention is low, the raw materials used are mainly natural minerals or industrial waste, and only a small amount of alkali and hydrogen peroxide are used; the preparation process is simple and does not involve energy-intensive process flows such as high temperature, ball milling, and hydrothermal. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The three-dimensional structure of the carbon dioxide adsorbent material of the bionic lung trachea structure of the present invention;
[0027] Figure 2 The pore size distribution diagrams of the adsorbent materials obtained in Example 1 and Comparative Example 1 are above 2 nm; Figure a is the pore size distribution diagram of Comparative Example 1, and Figure b is the pore size distribution diagram of Example 1;
[0028] Figure 3 The microscopic mineral composition and functional group structure of the adsorption materials obtained in Examples 1-3 and Comparative Examples 1-3; Figure a shows the microscopic mineral composition, and Figure b shows the functional group structure; in PGP-LLC 0.5wt%, PGP represents porous geopolymer, LLC represents landfill leachate concentrate, 0.5wt% represents the hydrogen peroxide content, and the same applies to the others;
[0029] Figure 4 The adsorption curve of CO2 under 4 cycles of adsorption / desorption of the adsorbent materials obtained in Examples 1-3 and Comparative Examples 1-3;
[0030] Figure 5 The isothermal adsorption curves of CO2 under variable pressure conditions for the adsorption materials obtained in Examples 1-3 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0031] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0032] Example 1
[0033] A carbon dioxide adsorbent material with a bionic lung trachea structure, the preparation method of which comprises the following steps:
[0034] S1. Dissolve 5 g of sodium hydroxide and 12 g of powdered sodium silicate in 24.2 g of landfill leachate concentrate (dissolved organic carbon is 450.9 mg / L), stir thoroughly for 5 min until completely dissolved, age for 12 h, and stir again twice during the ageing period to obtain a mixed solution;
[0035] S2. Add 30 g of ground blast furnace slag to the mixed solution obtained in step S1 and stir for 5 min until it becomes viscous to obtain a slurry. If the slurry coagulation rate increases and exhibits non-Newtonian fluid properties, add 1 mL of deionized water to the slurry and continue stirring for 2 min.
[0036] S3, add 0.36g hydrogen peroxide to the slurry obtained in step S2, stir evenly and let it stand for 2min to foam, the slurry volume increases, and a large number of bubbles are generated on the surface; then put it into 1×1×1cm 3 The silicone mold was sealed with plastic wrap, cured at 40°C for 12h, and demolded to obtain a carbon dioxide adsorption material with a bionic lung trachea structure.
[0037] Depend on Figure 2 It can be seen that the total porosity of the adsorption material obtained in Example 1 is 37.3%, the proportion of open pores is 98.4%, and the number of closed pores is 2.04×10 5 Pieces / cm 3 The porogen is mainly distributed in the range of 2nm-500μm, showing a stepped distribution.
[0038] Depend on Figure 4 It can be seen that the unconfined compressive strength of the adsorbent material obtained in Example 1 is 4.6 MPa, which has excellent mechanical stability. The isobaric adsorption (35°C) test results show that the average adsorption capacity of 4 cycles is 0.14 mmol / g, and the cycle loss is less than 1%, showing excellent cycle stability.
[0039] Depend on Figure 5 It can be seen that the adsorption capacity of the adsorption material obtained in Example 1 through pressure swing adsorption (25° C.) test is 0.25 mmol / g.
[0040] Example 2
[0041] A carbon dioxide adsorbent material with a bionic lung trachea structure, the preparation method of which comprises the following steps:
[0042] S1. Dissolve 4 g of sodium hydroxide and 13 g of powdered sodium silicate in 24.2 g of landfill leachate concentrate (dissolved organic carbon is 450.9 mg / L), stir thoroughly for 5 min until completely dissolved, age for 12 h, and stir again twice during the ageing period to obtain a mixed solution;
[0043] S2. Add 30 g of ground blast furnace slag to the mixed solution obtained in step S1 and stir for 5 min until it becomes viscous to obtain a slurry. If the slurry coagulation rate increases and exhibits non-Newtonian fluid properties, add 1 mL of deionized water to the slurry and continue stirring for 2 min.
[0044] S3, add 0.71g hydrogen peroxide to the slurry obtained in step S2, stir evenly and let it stand for 2min to foam, the volume of the slurry increases, and a large number of bubbles are generated on the surface; then put it into a 1×1×1cm 3 The silicone mold was sealed with plastic wrap, cured at 50°C for 12h, and demolded to obtain a carbon dioxide adsorption material with a bionic lung trachea structure.
[0045] Depend on Figure 4 It can be seen that the total porosity of the adsorbent material obtained in Example 2 is 48.2%, the unconfined compressive strength is 2.3 MPa, and it has good mechanical stability. The isobaric adsorption (35°C) test results show that the average adsorption capacity of 4 cycles is 0.22 mmol / g, and the cycle loss is less than 1%, showing excellent cycle stability.
[0046] Depend on Figure 5 It can be seen that the adsorption capacity of the adsorption material obtained in Example 2 obtained by pressure swing adsorption (25° C.) test is 0.31 mmol / g.
[0047] Example 3
[0048] A carbon dioxide adsorbent material with a bionic lung trachea structure, the preparation method of which comprises the following steps:
[0049] S1. Dissolve 5 g of sodium hydroxide and 12 g of powdered sodium silicate in 22 g of landfill leachate concentrate (dissolved organic carbon is 768.6 mg / L), stir thoroughly for 5 min until completely dissolved, age for 12 h, and stir again twice during the ageing period to obtain a mixed solution;
[0050] S2. Add 30 g of ground blast furnace slag to the mixed solution obtained in step S1 and stir for 5 min until it becomes viscous to obtain a slurry. If the slurry coagulation rate increases and exhibits non-Newtonian fluid properties, add 1 mL of deionized water to the slurry and continue stirring for 2 min.
[0051] S3, add 1.03g hydrogen peroxide to the slurry obtained in step S2, stir evenly and let it stand for 2min to foam, the volume of the slurry increases, and a large number of bubbles are generated on the surface; then put it into a 1×1×1cm 3 The silicone mold was sealed with plastic wrap, cured at 60°C for 12h, and demolded to obtain a carbon dioxide adsorption material with a bionic lung trachea structure.
[0052] Depend on Figure 4 It can be seen that the total porosity of the adsorbent material obtained in Example 2 is 49.6%, the unconfined compressive strength is 1.6 MPa, and the mechanical stability is good. The isobaric adsorption (35°C) test results show that the average adsorption capacity of 4 cycles is 0.21 mmol / g, and the cycle loss is less than 1%, showing excellent cycle stability.
[0053] Comparative Example 1
[0054] A carbon dioxide adsorption material is different from Example 1 in that, in step S1, deionized water is used instead of landfill leachate concentrate.
[0055] Depend on Figure 2 It can be seen that the total porosity of the adsorption material obtained in Comparative Example 1 is 38.6%, the proportion of open pores is 99.1%, and the number of closed pores is 7.75×10 4 Pieces / cm 3 The porogen is mainly distributed in the range of 2nm-500μm, without showing a step distribution.
[0056] Depend on Figure 3It can be seen that the adsorption material obtained in Comparative Example 1 is mainly an amorphous aluminosilicate structure, and contains a large number of ≡Si-OH / ≡Al-OH active sites on the surface.
[0057] Depend on Figure 4 It can be seen that the unconfined compressive strength of the adsorption material obtained in Comparative Example 1 is 3.5 MPa, and the isobaric adsorption (35° C.) test result is that the average adsorption amount after 4 cycles is 0.05 mmol / g, the cycle loss is greater than 1%, and the cycle stability is weakened.
[0058] Depend on Figure 5 It can be seen that the adsorption capacity of the adsorption material obtained in Comparative Example 1 by pressure swing adsorption (25° C.) test is 0.06 mmol / g.
[0059] Comparative Example 2
[0060] A carbon dioxide adsorbent material, which is different from Example 1 in that hydrogen peroxide is not added in step S3.
[0061] Depend on Figure 3 It can be seen that the total porosity of the adsorption material obtained in Comparative Example 2 is 15.6%, the unconfined compressive strength is 12.1 MPa, and the mechanical stability is excellent. The isobaric adsorption (35°C) test results show that the average adsorption amount after 4 cycles is 0.09 mmol / g, and the cycle loss amount reaches 60.6%, which means there is almost no cycle stability.
[0062] Depend on Figure 4 It can be seen that the adsorption material obtained in Comparative Example 2 still did not reach adsorption equilibrium within 20 minutes. The adsorption amount obtained by pressure swing adsorption (25° C.) test was 0.06 mmol / g.
[0063] Comparative Example 3
[0064] A carbon dioxide adsorbent material, which is different from Example 1 in that a block material is ground into powder using a mortar.
[0065] Depend on Figure 4 It can be seen that the isobaric adsorption (35° C.) test results of the adsorption material obtained in Comparative Example 3 showed that the average adsorption capacity after 4 cycles was 0.06 mmol / g, and the cycle loss reached 39.1%, with almost no cycle stability.
[0066] In summary, hydrogen peroxide and foam stabilizers are key factors in obtaining biomimetic lung tracheal structures, which can adjust the pores to achieve carbon dioxide capture. Compared with unfoamed or powdered adsorbents, the carbon dioxide adsorption capacity, adsorption rate and cyclic stability of the adsorbent material with biomimetic lung tracheal structure are significantly improved.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon dioxide adsorbent material with a bionic lung trachea structure, characterized in that: The following steps are involved: S1. dissolving alkali and active silica in the landfill leachate concentrate containing a foam stabilizer, stirring until completely dissolved, and aging to obtain a mixed solution; S2, adding activated alumina to the mixed solution obtained in step S1, stirring until viscous, to obtain a slurry; S3, adding hydrogen peroxide to the slurry obtained in step S2, stirring evenly and letting it stand for foaming, then filling it into a silicone mold, and then sealing, curing and demoulding in sequence to obtain a carbon dioxide adsorption material with a bionic lung trachea structure.
2. The method for preparing the carbon dioxide adsorbent material of the bionic lung trachea structure according to claim 1, characterized in that: In step S1, the alkali is sodium hydroxide or potassium hydroxide; and the active silicon dioxide is sodium silicate or potassium silicate.
3. The method for preparing the carbon dioxide adsorbent material of the bionic lung trachea structure according to claim 1, characterized in that: In step S1, the foam stabilizer is at least one of lignin, molasses, humic acid and fulvic acid; and its content is 80-2000 mg / L in terms of dissolved organic carbon.
4. The method for preparing the carbon dioxide adsorbent material of the bionic lung trachea structure according to claim 1, characterized in that: In step S1, the mixture is aged for 12 hours and stirred again 2-3 times during the aging period.
5. The method for preparing the carbon dioxide adsorbent material of the bionic lung trachea structure according to claim 1, characterized in that: In step S2, the activated alumina is at least one of metakaolin, ground blast furnace slag, fly ash and red mud.
6. The method for preparing the carbon dioxide adsorbent material of the bionic lung trachea structure according to claim 1, characterized in that: In step S2, the liquid-to-solid ratio of the slurry is 0.5-0.
7.
7. The method for preparing the carbon dioxide adsorbent material of the bionic lung trachea structure according to claim 1, characterized in that: In steps S1 and S2, the mass ratio of alkali, activated silicon dioxide and activated aluminum oxide is 3-7:18-22:3-7.
8. The method for preparing the carbon dioxide adsorbent material of the bionic lung trachea structure according to claim 1, characterized in that: In step S3, the amount of hydrogen peroxide added is 0.5-3wt% of the slurry.
9. The method for preparing the carbon dioxide adsorbent material of the bionic lung trachea structure according to claim 1, characterized in that: In step S3, the silicone mold is sealed with plastic wrap and cured at a temperature of 40-70° C. for 12 hours.
10. The carbon dioxide adsorbent material with a bionic lung trachea structure obtained by the method for preparing the carbon dioxide adsorbent material with a bionic lung trachea structure according to any one of claims 1 to 9.
Citation Information
Patent Citations
Novel multi-metal MOF (Metal Organic Framework) material as well as preparation method and application thereof
CN116037078A
Preparation method of nitrogen and boron modified coal-based activated carbon for carbon dioxide adsorption
CN116062751A
Method for removing carbon dioxide in biogas by roasting magnesium-aluminum hydrotalcite
CN117025272A
Post-treatment modification method for strengthening zeolite carbon capture and adsorption dehumidification performance
CN117699815A